Desafios à conservação de áreas protegidas no estado de Mato Grosso (Brasil) : o caso do Parque Estadual Cristalino - Rocha, Paula Caroline Meira (2020)
This paper aims to identify the threats faced by protected areas in the state of Mato Grosso for their conservation. It was studied the emergence of protected areas in Brazil and around the world, the creation of the National System of Nature Conservation Units and the objectives of protected areas in the country. The relevance of environmental conservation and of the biodiversity of the state of Mato Grosso and the federal, state and municipal conservation units currently present in the state are evaluated at the regional range. Common problems existing in state protected areas related to supervision and implementation by the state agency responsible for managing these areas are identified. The aim is to study the problems faced in protected areas already established in the state of Mato Grosso, such as the overlapping of indigenous lands and conservation units, unresolved land issues, political pressures and the existence of bills to reduce already established protected areas, and the public policies used in the implementation of these areas, encompassing the management and structure in the public agencies responsible for the inspection of protected areas. The study involved bibliographic and documentary research, using the deductive method to address the specific challenges faced the Cristalino State Park, located in the extreme north of Mato Grosso state, encompassing the characterization and creation of this Conservation Units, the existing pressures to reduce the protected area and the current situation of deforestation in and around the mentioned Park.